Genetic and neurodevelopmental spectrum of SYNGAP1-associated intellectual disability and epilepsy. Issue 8 (17th March 2016) - Mignot, Cyril; von Stülpnagel, Celina; Nava, Caroline; Ville, Dorothée; Sanlaville, Damien; Lesca, Gaetan; Rastetter, Agnès; Gachet, Benoit; Marie, Yannick; Korenke, G Christoph; Borggraefe, Ingo; Hoffmann-Zacharska, Dorota; et al.
Abstract : Objective: We aimed to delineate the neurodevelopmental spectrum associated with SYNGAP1 mutations and to investigate genotype–phenotype correlations. Methods: We sequenced the exome or screened the exons of SYNGAP1 in a total of 251 patients with neurodevelopmental disorders. Molecular and clinical data from patients with SYNGAP1 mutations from other centres were also collected, focusing on developmental aspects and the associated epilepsy phenotype. A review of SYNGAP1 mutations published in the literature was also performed. Results: We describe 17 unrelated affected individuals carrying 13 different novel loss-of-function SYNGAP1 mutations. Developmental delay was the first manifestation of SYNGAP1 -related encephalopathy; intellectual disability became progressively obvious and was associated with autistic behaviours in eight patients. Hypotonia and unstable gait were frequent associated neurological features. With the exception of one patient who experienced a single seizure, all patients had epilepsy, characterised by falls or head drops due to atonic or myoclonic seizures, (myoclonic) absences and/or eyelid myoclonia. Triggers of seizures were frequent (n=7). Seizures were pharmacoresistant in half of the patients. The severity of the epilepsy did not correlate with the presence of autistic features or with the severity of cognitive impairment. Mutations were distributed throughout the gene, but spared spliced 3′ and 5′ exons. Seizures in patients with mutations in exons 4–5 were more pharmacoresponsive than in patients with mutations in exons 8–15. Conclusions: SYNGAP1 encephalopathy is characterised by early neurodevelopmental delay typically preceding the onset of a relatively recognisable epilepsy comprising generalised seizures (absences, myoclonic jerks) and frequent triggers.